الفروق بين مرتفعي ومنخفضي الشفقة بالذات في كل من اجترار الأفكار والاحتراق الأكاديمي لدى المتفوقين عقليا ذوي التفريط التحصيلي بالمرحلة الثانوية - مصطفى، ميهان حمدي محمد (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2024)
هدف البحث الحالي إلى التعرف على الفروق بين مرتفعي ومنخفضي الشفقة بالذات في كل من اجترار الأفكار والاحتراق الأكاديمي لدى المتفوقين عقليا ذوي التفريط التحصيلي بالمرحلة الثانوية، واستخدمت الباحثة المنهج الوصفي المقارن، وتم تطبيق مقياس الشفقة بالذات إعداد الباحثة، ومقياس اجترار الأفكار إعداد (Tanner, Voon, Hasking, & Martin: 2013) وترجمة الباحثة، ومقياس الاحتراق الأكاديمي إعداد الباحثة واستخدمت الباحثة اختبار "ت" لعينتين مستقلتين للتحقق من صحة فروض الدراسة، وأسفرت نتائج البحث عن وجود فروق بين مرتفعي ومنخفضي الشفقة بالذات في اجترار الأفكار لصالح منخفضي الشفقة بالذات، ووجود فروق بين مرتفعي ومنخفضي الشفقة بالذات في الاحتراق الأكاديمي لصالح منخفضي الشفقة بالذات، كما أظهرت النتائج وجود فروق بين كل من الذكور مرتفعي ومنخفضي الشفقة بالذات في اجترار الأفكار لصالح منخفضي الشفقة بالذات، ووجود فروق بين الإناث منخفضات ومرتفعات الشفقة بالذات في اجترار الأفكار لصالح منخفضات الشفقة بالذات، كما أظهرت النتائج وجود فروق بين الذكور مرتفعي ومنخفضي الشفقة بالذات في الاحتراق الأكاديمي لصالح منخفضي الشفقة بالذات، ووجود فروق بين الإناث منخفضات ومرتفعات الشفقة بالذات في الاحتراق الأكاديمي لصالح منخفضات الشفقة بالذات. The aim of the current research was to identify the Differences between high and low self-compassion in Rumination and Academic Burnout for Mentally Gifted-underachievers Students in High School. The researcher used the descriptive-comparative method. The self-compassion scale and academic burnout scale prepared by the researcher and the rumination scale prepared by the (Tanner, Voon, Hasking, & Martin: 2013) was applied. The researcher used a t-test for two independent samples to verify the validity of the study hypotheses. The results of the research revealed differences between those with high and low self-compassion in rumination, in favor of those with low self-compassion, there are differences between those with high and low self-compassion in academic burnout in favor of those with low self-compassion. The results also showed that there were differences between both males with high and low self-compassion in rumination in favor of those with low self-compassion, there are differences between females with low and high self-compassion in rumination in favor of those with low self-compassion, The results also showed that there were differences between males with high and low self-compassion in academic burnout in favor of those with low self-compassion. There are differences between females with low and high self-compassion in academic burnout in favor of those with low self-compassion.
Keywords: اليقظة العقلية -- الإرشاد النفسي -- التحصيل الأكاديمي -- طلبة الجامعات